Dinoflagellates, a Unique Lineage for Retrogene Research - Song, Bo; Chen, Sijie; Chen, Wenbin (Frontiers in Microbiology, 2018)
The birth and evolution of retrogenes have played crucial roles in genome evolution. Dinoflagellates represent a unique lineage for retrogene research because the retrogenes can be reliably identified by the presence of a 22 nucleotide splice leader DinoSL, which is post-transcriptionally added to the 5’ terminus of all mRNAs. Compared to studies of retrogenes conducted in other model genomes, dinoflagellate retrogenes can potentially be more comprehensively characterized because intron-containing retrogenes have already been detected. Unfortunately, dinoflagellate retrogene research has long been neglected. Here we review the work on dinoflagellate retrogenes and show their distinct character. Like the dinoflagellate genome itself, dinoflagellate retrogenes are also characterized by many unusual features, including a high survival rate and large numbers in the genome. These data are critical complements to what we know about retrogenes, and will further frame our understanding of retroposition and its roles in genome evolution, as well as providing new insights into retrogene studies in other genomes.